Methane adsorption behavior on shale matrix at in-situ pressure and temperature conditions: Measurement and modeling. (15th September 2018) - Chen, Mingjun; Kang, Yili; Zhang, Tingshan; Li, Xiangchen; Wu, Keliu; Chen, Zhangxin
Highlights: Methane adsorption experiments on shales were conducted at in-situ conditions. Excess adsorption phenomenon was explained for gravimetric method. The influences of shale gas adsorption capacity were analyzed. A SLD adsorption model considering the cylindrical pore geometry was established. Abstract: Adsorbed gas is a significant component of shale gas due to the abundant nanopores of organic matter in shales. Methane adsorption behavior on shale matrix is complex considering the geochemical properties, lithology, pore structure and pressure-temperature conditions. In this work, methane adsorption experiments were conducted through a gravimetric method for shale samples at reservoir pressure and temperature conditions. Meanwhile, total organic carbon (TOC), mineral contents and pore structure parameters of samples were measured, respectively. Experimental results show that (1) an excess adsorption phenomenon is obvious at high-pressure and high-temperature conditions; (2)methane adsorption capacity of shale tends to increase with an increase of TOC; (3) lithology and pore structure also affect the methane adsorption capacity of shales, inducing the different adsorption results of two samples with similar TOC; (4) a shale with a large TOC, a low illite content, a large specific area, a large pore volume and a small average diameter would have a strong methane adsorption capacity, nevertheless the effect of TOC is generally dominant. In order to further investigate the methane adsorption behavior on shales, a simplified local density adsorption model considering the cylindrical pore geometry is established, and is regressed and verified by the experimental data. The modeling results indicate that a sample with a large TOC would have a strong fluid-solid interaction energy and a large surface area of methane adsorption. At last, the mechanism of methane adsorption on shales at in-situ conditions is summarized. This work is beneficial for an accurate shale gas reservoir modeling.